Kapasitas Petani Penangkar Benih Padi di Kabupaten Majalengka: Peran Penyuluhan dan Kelompok Tani - Atang Muhammad Safei; Siti Amanah; Anna Fatchiya (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2021)
The availability of certified rice seeds is still limited because the limited number of rice seed breeder farmers.The capacity of farmers in seed assessment and seed production determine the succes of the rice seed breeding. The research using the census method (112 breeder farmers) was conducted in Majalengka Regency. Interviews and observations were carried out to obtain data on extension and breeding of rice seeds by farmers. Partial Least Square (PLS-Path Modeling) was used to analyze the data. The results showed that the suitability of the materials, extension methods and ability of the extension agents were in the medium category, the intensity of extension was still low. Extension officers visit farmer groups once a month. The role of farmer groups and farmer capacity is in the medium category. Farmer groups are able to carry out the learning process and seed production even though the marketing is not continuous. The implementation of extension services and farmer groups has a positive effect on the farmer capacity. The use of social media by breeder farmers for seed marketing and obtaining marketing partners and business capital can be increased through increasing the intensity of extension by involving farmer groups.